Effect of interleukins (IL-2, IL-15, IL-18) on receptors activation and cytotoxic activity of natural killer cells in breast cancer cell - Widowati, Wahyu; Jasaputra, Diana K; Sumitro, Sutiman B; Widodo, Mochammad A; Mozef, Tjandrawati; Rizal, Rizal; Kusuma, Hanna Sari W; Laksmitawati, Dian R; Murti, Harry; Bachtiar, Indra; Faried, Ahmad (African health sciences, 2020)
Introduction: Breast cancer is one of the leading cause of cancer deaths in women. Metastasis in BC is caused by immunosurveillance deficiency, such NK cell maturation, low NK activity and decreasing cytotoxicity. This study was performed to improve activating receptors and cytotoxicity of NK cells using interleukins (ILs). Methods: Human recombinant IL-2, -15, and -18 were used to induce NK cells. We measured the activating and inhibiting receptors, proliferation activity of NK cells, and the cytotoxicity of NK cells on BC cells (MCF7). The effects of ILs were tested on the NK cell receptors CD314, CD158a and CD107a with flowcytometry, proliferation at various incubation times with 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxy methoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay and concentrations of TNF-α and IFN-γ by NK cells with ELISA. Results: ILs increased NK cell receptor levels (CD314, CD158a, and CD107a) at 24 hours of incubation. ILs increased NK cell viability, which increased with longer incubation. Moreover, ILs-induced NK cells inhibited proliferation in MCF7 cells, as well as increased TNF-α, IFN-γ, PRF1 and GzmB secretion. Conclusion: IL-2, IL-15, and IL-18 improved activating receptors and proliferation of NK cells. IL-induced NK cells increased TNF-α, IFN-γ, PRF1 and GzmB secretion and cytotoxic activity on BC cells. High NK cell numbers increased BC cell growth inhibition.